The Role of Government Policy and Stakeholder Engagement In Improving Performance of MSMEs In North Kayong Regency - Adi Mursalin; Windi Pratiwi; Ricola Dewi Rawa; Angga Hendharsa; Aisyah Aisyah (Green Publisher Indonesia, 2022)
This study aims to examine the role of government policies and stakeholder involvement in improving the performance of MSMEs in North Kayong Regency. This research uses a mix method. The population in this study were MSME actors in North Kayong Regency, totaling 7,687 MSME actors. Sample selection using purposive sampling and quota sampling techniques. The data collection techniques used were interviews, questionnaires, documentary studies and literature studies. The analysis method used is multiple regression analysis using statistical software SPSS 26.0. The results showed that for the role of government policy, the funding aspect indicator had a significant value of 0.000 (p-value 0.000 <0.05). The facilities and infrastructure aspect has a significant value of 0.213 (p-value 0.213> 0.05). The business information aspect has a significant value of 0.010 (p-value 0.010 < 0.05). The partnership aspect has a significant value of 0.002, (p-value 0.002 < 0.05). The licensing aspect has a significance value of 0.008 (p-value 0.008 < 0.05). The business opportunity aspect has a significance value of 0.001 (p-value 0.001 <0.05). The trade promotion aspect has a significance value of 0.749 (p-value 0.749 > 0.05). Furthermore, for stakeholder involvement, namely financial institutions have a significance value of 0.034 (p-value 0.034 < 0.05) and business associations have a significance value of 0.110 (p-value 0.110 > 0.05)